Conflict and Violence: Training Content in the Degrees in Journalism from Spanish Universities - Galván Arias, María Ángeles (Historia y Comunicación Social, 2014)
In the studies programs of a degree in Journalism from Spain it is strikingly poor the presence of subjects that oriented specialized mode toward the formation and training of the students in the matters linked with the information on the facts and events relating to conflict and violence (armed conflict, terrorism, gender violence, bullying, gangs, violence in sports, industrial disputes) despite the social significance and professional thematic area. The phenomenon is compounded by the significant optional nature of the educational offer.